Cytoplasmic polyadenylation element-binding protein 4 is highly expressed in human glioma. Issue 8 (25th May 2016) - Hu, Hongchao; Cong, Lulu; Liang, Chaohui; Yang, Liang; Guo, Erkun; Song, Jian; Liu, Liqiang; Lu, Shengkui; Guo, Chengyong; Wu, Zhendong; Ma, Shucheng; Zhao, Zongmao; et al.
Abstract : Cytoplasmic polyadenylation element-binding protein 4 (CPEB4) is a highly conserved, sequence-specific RNA-binding protein that recruits translational repression or cytoplasmic polyadenylation machinery to target mRNAs. Recent studies have shown that CPEBs are expressed in somatic tissues and have essential functions supporting tumor growth, vascularization, and invasion. Overexpression of CPEB4 has been reported in pancreatic ductal adenocarcinoma and is associated with poor prognoses. However, whether CPEB4 plays a role in the tumorigenesis of gliomas is unknown. Here, we analyzed the expression of CPEB4 in gliomas. The expression profiles of CPEB4 mRNA and protein in nine normal brain tissues and 63 gliomas were detected using immunohistochemistry, real-time PCR, and western blotting. CPEB4-positive expression was significantly correlated with the pathological grade of glioma; abundant expression was observed in high-grade gliomas, whereas little or no expression was observed in normal astrocytes. Immunohistochemistry staining indicated that CPEB4 was mainly localized in the cytoplasm. In addition, CPEB4 was more highly expressed in U87 glioma cells than in U251 cells. CPEB4 expression significantly correlated with the grade in clinical gliomas. This study suggested that CPEB4 might play a role in the pathogenesis of glioma.